2015
DOI: 10.1039/c5cp02453f
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene-based materials for solar cell applications: design of novel acceptors for efficient polymer solar cells – a DFT study

Abstract: Fossil fuel alternatives, such as solar energy, are moving to the forefront in a variety of research fields. Polymer solar cells (PSCs) hold promise for their potential to be used as low-cost and efficient solar energy converters. PSCs have been commonly made from bicontinuous polymer:fullerene composites or so-called bulk heterojunctions. The conjugated polymer donors and the fullerene derivative acceptors are the key materials for high performance PSCs. In the present study, we have performed density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 63 publications
(140 reference statements)
2
30
0
1
Order By: Relevance
“…For pristine fullerenes, the charge distribution is generally homogenously allocated, and some regions are colored in blue, meaning that they present low electron density. This concurs with reports that indicate that fullerenes can act as electron acceptor systems . Contrarily, boron‐doped fullerenes present a significantly low electron density region in the vicinity of the boron atom.…”
Section: Resultssupporting
confidence: 92%
“…For pristine fullerenes, the charge distribution is generally homogenously allocated, and some regions are colored in blue, meaning that they present low electron density. This concurs with reports that indicate that fullerenes can act as electron acceptor systems . Contrarily, boron‐doped fullerenes present a significantly low electron density region in the vicinity of the boron atom.…”
Section: Resultssupporting
confidence: 92%
“…They have a hydrophobic character, high electron affinity and high surface to volume ratio, and surface defects. These unique physicochemical properties make them an ideal material for various applications such as semiconductors, electronics, biomedical sciences, solar cells, sensors, cosmetics, artificial photosynthesis, and surface coatings [50–52]. Brunet et al showed that hydrophilic functionalized fullerenes (C 60 ) have also been applied for the killing of the pathogenic microorganisms in water by utilizing a photocatalytic process.…”
Section: Classification Of Carbon Nanomaterials Based On Their Dimensmentioning
confidence: 99%
“…Over the years, a sharp increase in the usage of these materials in various industry and health fields resulted in their copious release into the environment and aquatic biota [3,4]. Carbon 60 nanoparticles (C 60 NPs) have been used in many commercial processes and industrial products such as IT (intelligent technology) devices and diagnostics, as well as in environmental, pharmaceutical, superconductor, and energy industries [5,6]. Fullerenes are the third pure form of carbon.…”
Section: Introductionmentioning
confidence: 99%